بر صغیر میں علم حدیث کی نشر و اشاعت اور محدثین کرام کی خدمات کا علمی جائزہ: Analytical study of the propagation of Ḥadīth-learning and the services of Muḥaddithīn in the Subcontinent - Haq, Fazal; Fareed ud din, Hafiz (Al-Amīr Research Journal for Islamic Studies, 2020)
Ḥadīth learning has a very high status in Islamic education after the Exegesis of the Holy Qurān (Tafsīr). Oddly enough, Non-Arab (‘Ajam) has a more important and key role than Arabs in the service of this knowledge. In this regard, the subcontinent is also being remained in the forefront. It started when Muhammad bin Qasim strengthened the Arab government in Sindh. Sheikh Abdul Haq Muhaddith Dehalvi is one of the prominent names in the teaching and writing of ḥadīth which travels gradually and reaches the family of Shah Waliullah, which is undoubtedly the pinnacle of ḥadīth knowledge in the subcontinent. The types of hadith that have been worked on, in connection with the service of ḥadīth, include the text of ḥadīth, commentaries, as well as summaries of ḥadīth and others. The entire Islamic world has benefited from all these teaching and writing services. The subcontinent, especially Pakistan, is gaining a central position in the Islamic world, which is the result of the propagation of Islam and understanding of the Qurān and Ḥadīth. In this regard, it is imperative to re-evaluate the services of the historians of this land. The said article will not only provide an introductory review of the Muḥaddith in the subcontinent and their authorship as well as a compilation but will also highlight the broadcasting and writing services of the hadith learning.